Exploring the composition and structure of milk and meat value chains, food safety risks and governance in the Addis Ababa and Oromia regions of Ethiopia - Ndungu S. Nyokabi; Johanna F. Lindahl; Johanna F. Lindahl; Johanna F. Lindahl; Lisette T. Phelan; Stefan Berg; Gizachew Gemechu; Adane Mihret; James L. N. Wood; Henrietta L. Moore (Frontiers in Sustainable Food Systems, 2023)
Demand for animal-source foods (ASF) is increasing globally, driven by population growth and changing dietary preferences. In global south countries, low compliance with good agricultural practices (GAPs) and food safety standards in the production of ASF is a major public health concern due to the high prevalence of foodborne diseases. This study examines the composition and structure of milk and meat value chains and explores food safety risks and governance in the Addis Ababa and Oromia regions of Ethiopia. Stakeholder discussions, key informant interviews and participant observation were undertaken to collect data on milk and meat value chain actors' perceptions of opportunities and constraints to improving access to safe, high-quality milk and meat products. The results reveal low compliance with rules and standards by milk and meat value chain actors which could compromise food safety and quality and expose consumers to public health risks. There was stricter enforcement of GAPs and food safety standards in the case of milk and meat products destined for export compared to products sold in the local market. The main barriers to compliance with food safety regulations were actors' low knowledge, small profit margins, absence of critical food safety infrastructure such as electricity and road and low access to capital to invest in the recommended equipment such as aluminum containers, coolers and fridges. This paper concludes there is a need for targeted efforts to support the adoption of low-cost technologies that could mitigate food safety risks. Additionally, there is a need for improved communication and tailored training for value chain actors that reflect local social, cultural and economic context to incentivise compliance with rules governing food safety and quality.